Migration patterns of the Osprey Pandion haliaetus on the Eastern European–East African flyway. (2nd January 2016) - Väli, Ülo; Sellis, Urmas
Abstract : We analysed migration strategies of the Osprey Pandion haliaetus on the poorly studied Eastern European–East African flyway. Four adult birds were equipped with GPS-based satellite-transmitters or data-loggers in their breeding sites in Estonia (north-eastern Europe) and tracked to their wintering grounds in Africa and back, during up to six migration cycles. Departure times, migration routes, as well as wintering and stopover sites varied remarkably between individuals but not much between years. Stopovers (2–30 days) were made mostly in Europe and less in the Middle East (Turkey) and north-eastern Africa (Egypt). The Ospreys did not avoid flying long distances over the sea, and the sea was crossed four times during the night. The current study adds to current knowledge on Osprey migration and should help to concentrate actions on protecting important flyways and stopover locations.